Effects of sports training and psychological training on employees’ psychological stress - Xue Wu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Physical exercise and psychological training can offer additional interpersonal possibilities for college students, allowing them to actively participate in activities while also enhancing their interpersonal skills, mood, and life outlook. This study aims to examine the effect of sports and psychological training on the psychological stress of Chinese employees. In this study, 110 convenient sampling techniques were used to select 115 male university volunteers in public physical education as experimental participants, who were then randomly divided into experimental class and control class, and the psychological pressure and changes in various dimensions were evaluated using the natural experiment method. Using SPSS21.0, mathematical-statistical analysis was done on the recovered accurate scales. After 12 weeks of psychological intervention, the psychological training group had significant differences in the dimensions of life (P = 0.030), development (P = 0.013) and social (P = 0.016) (P < 0.05), family (P = 0.000), life events (P = 0.001) and total score (P = 0.002) (P < 0.01). The exercise intensity was controlled within the range of medium and small intensity and did not receive psychological training, but some dimensions had positive changes. Psychological training can significantly reduce the psychological pressure of the development dimension. Moderate intensity exercise combined with psychological training is beneficial for coping with psychological pressure, and its positive regulation effect is significantly superior to physical exercise or psychological training alone. Therefore, the total impact of physical exercise combined with psychological training intervention is still evident and should be promoted.